MALARIA DIAGNOSIS BY LOOP-MEDIATED ISOTHERMAL AMPLIFICATION (LAMP) IN THAILAND - Ronja OCKER; Yongyut PROMPUNJAI; Salakchit CHUTIPONGVIVATE; Panagiotis KARANIS (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
The loop-mediated isothermal amplification method (LAMP) is a recently developed molecular technique that amplifies nucleic acid under isothermal conditions. For malaria diagnosis, 150 blood samples from consecutive febrile malaria patients, and healthy subjects were screened in Thailand. Each sample was diagnosed by LAMP, microscopy and nested polymerase chain reaction (nPCR), using nPCR as the gold standard. Malaria LAMP was performed using Plasmodium genus and Plasmodium falciparum specific assays in parallel. For the genus Plasmodium, microscopy showed a sensitivity and specificity of 100%, while LAMP presented 99% of sensitivity and 93% of specificity. For P. falciparum, microscopy had a sensitivity of 95%, and LAMP of 90%, regarding the specificity; and microscopy presented 93% and LAMP 97% of specificity. The results of the genus-specific LAMP technique were highly consistent with those of nPCR and the sensitivity of P. falciparum detection was only marginally lower.